Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/1754-9485.12779
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of lung adenocarcinoma: A pictorial essay

Abstract: Lung adenocarcinoma has a spectrum of appearances on CT, many of which mimic non-malignant processes. The general radiologist has a major role in guiding the management of abnormalities detected on chest CT and an awareness of these appearances is vital. We describe the protean imaging manifestations of lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 13 publications
0
29
0
2
Order By: Relevance
“…Lesions are usually solitary but can also be multifocal. In a few instances, calcification or cavitation can be seen making it difficult to distinguish from infectious diseases like tuberculosis, pneumonia, or fungal infections [11] (will need more references). The adenocarcinoma's histologic growth pattern is mostly acinar, papillary, and solid; therefore the surfaces in the lobes often have small differentiated leaves and spinous processes [10].…”
Section: Discussionmentioning
confidence: 99%
“…Lesions are usually solitary but can also be multifocal. In a few instances, calcification or cavitation can be seen making it difficult to distinguish from infectious diseases like tuberculosis, pneumonia, or fungal infections [11] (will need more references). The adenocarcinoma's histologic growth pattern is mostly acinar, papillary, and solid; therefore the surfaces in the lobes often have small differentiated leaves and spinous processes [10].…”
Section: Discussionmentioning
confidence: 99%
“…According to He et al, breast and lung cancer account for 37.2% and 24.2% of pituitary metastatic lesions, respectively (10). The main particularity in LAC consists in a large spectrum of appearances and may not appear on the classical chest radiography as it was in our case (11). This should lead to further investigation with cross-sectional imaging at this stage, including basic pathology and CT imaging of the neck, chest, abdomen and pelvis (12).…”
Section: Discussionmentioning
confidence: 60%
“…The green lines indicated that acetylation of the enzymes, which mediated the specific chemical reaction, was significantly reduced cases. In contrast to other types of lung cancer, lung adenocarcinoma typically develops more slowly [29,30]. Numerous studies have shown that genetic and epigenetic alterations play a critical role in oncogenesis and the progression of tumors.…”
Section: Discussionmentioning
confidence: 99%